Average Ambulatory Measures of Sound Pressure Level, Fundamental Frequency, and Vocal Dose Do Not Differ Between Adult Females With Phonotraumatic Lesions and Matched Control Subjects - Van Stan, Jarrad H; Mehta, Daryush D; Zeitels, Steven M; Burns, James A; Barbu, Anca M; Hillman, Robert E (Annals of otology, rhinology & laryngology, 2015)
Clinical management of phonotraumatic vocal fold lesions (nodules, polyps) is based largely on assumptions that abnormalities in habitual levels of sound pressure level (SPL), fundamental frequency (f0), and/or amount of voice use play a major role in lesion development and chronic persistence. This study used ambulatory voice monitoring to evaluate if significant differences in voice use exist between patients with phonotraumatic lesions and normal matched controls. Subjects were 70 adult females: 35 with vocal fold nodules or polyps and 35 age-, sex-, and occupation-matched normal individuals. Weeklong summary statistics of voice use were computed from anterior neck surface acceleration recorded using a smartphone-based ambulatory voice monitor. Paired t tests and Kolmogorov-Smirnov tests resulted in no statistically significant differences between patients and matched controls regarding average measures of SPL, f0, vocal dose measures, and voicing/voice rest periods. Paired t tests comparing f0 variability between the groups resulted in statistically significant differences with moderate effect sizes. Individuals with phonotraumatic lesions did not exhibit differences in average ambulatory measures of vocal behavior when compared with matched controls. More refined characterizations of underlying phonatory mechanisms and other potentially contributing causes are warranted to better understand risk factors associated with phonotraumatic lesions.